Review of song patterns and sound production in armoured ground crickets (Orthoptera: Tettigoniidae: Hetrodini) with karyological data and taxonomic notes - Heller, Klaus-Gerhard; Chobanov, Dragan; Warchałowska-Śliwa, Elżbieta; Hemp, Claudia (Zootaxa, 2022)
In the mate finding system of bush-crickets, acoustical signals play a central role. Here we review and describe the bioacoustics of Hetrodini, a morphologically uniform group of Tettigonioidea with a distribution centered in Africa. The male calling songs are produced by tegmino-tegminal stridulation. In all species, these fore wings are completely covered by the pronotum (invisible in intact specimens) and lack the glossy mirror cells which are well-known from many other singing Ensifera. Concerning spectral composition, the broad frequency peak and the parts with the most energy lie in the high audio or low ultrasonic range. In amplitude modulation, the songs are relatively simply structured and contain only one type of syllables each. These syllables consist of heavily dampened impulses (non-resonant song) and are arranged in long series of echemes (chirps) or trills. As far as it is known, syntopic species differ in syllable and/or echeme repetition rates. In contrast to the uniform morphology, the karyotypes are surprisingly diverse with chromosome numbers ranging from 2n = 29 to 17 and one of two sex determination systems: X0 and neo-XY. In our opinion, taxonomically the group is at the moment at best considered as a tribe incertae sedis (without subfamily classification) within Tettigoniidae (not Tettigoniinae sensu OSF).